The Effect of Employees’ Behavioral Competency Units on Organizational Effectiveness: The Case of Selected Public Service Institutions of Ethiopia - Abadama, Desalegn Sherkabu Abadama (African Journal of Leadership and Development, 2024)
Organizational effectiveness, a common measure of entities, is noted for being a vital metrics. It is this vital attribute of organizations’ employees’ behavioral competency units that was under close scrutiny here based on data methodologically collected from 394 employees. A cross-sectional survey design and a corresponding set of sound analytic techniques along with a SEM model was employed using version 24 AMOS-supported SPSS. The analysis witnessed a strong interconnectivity among the various dimensions of the competency units on organizational effectiveness as regards the various independent variables. However, the findings of the investigation proved that staffs’ perceived-people-oriented competencies registered only a very low effect on organizational effectiveness nevertheless. This might be attributable to the task-orientated organizational culture that may need further investigation. The qualitative data collected from both individual informants via a focus group discussion brought both positive and negative responses. Consequently, the researcher put forward viable recommeddations to deal with the issue investigated.